Studi Literatur: Game-Based Learning Berbantuan Wordwall untuk Meningkatkan Minat dan Hasil Belajar Siswa Sekolah Dasar - Desta Puspa Aulia; Dewi Indrapangastuti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The advancement of digital technology has brought significant changes to education, including at the elementary school level. One of the challenges faced is the low level of student interest and learning outcomes due to instructional methods that do not align with the characteristics of the digital generation. This study aims to examine the effectiveness of the game-based learning model supported by Wordwall  in enhancing students’ interest and learning outcomes in elementary education. The method used is a literature review of 30 scholarly articles published between 2020 and 2024, sourced from Google Scholar, Garuda, and Sinta, and selected through stages of identification, screening, and eligibility assessment. The findings show that Wordwall  can improve student engagement, motivation, and learning initiative, while also positively influencing learning outcomes, including academic scores, mastery, and critical thinking skills. Wordwall  aligns with student-centered learning principles and supports the implementation of the Kurikulum Merdeka, making it a relevant and effective tool for addressing educational challenges in the digital era. The findings conclude that Wordwall offers an enjoyable and interactive learning experience, stimulates active participation, and enhances student attention during lessons. Kemajuan teknologi digital telah mendorong perubahan signifikan dalam pendidikan, termasuk di tingkat sekolah dasar. Salah satu tantangan yang dihadapi adalah rendahnya minat dan hasil belajar siswa akibat metode pembelajaran yang tidak sesuai dengan karakteristik generasi digital. Penelitian ini bertujuan mengkaji efektivitas model game-based learning berbantuan Wordwall  dalam meningkatkan minat dan hasil belajar siswa sekolah dasar. Metode yang digunakan adalah studi literatur terhadap 30 artikel ilmiah terbitan 2020–2024, yang diperoleh dari Google Scholar, Garuda, dan Sinta, lalu diseleksi melalui tahapan identifikasi, penyaringan, dan uji kelayakan. Hasil kajian menunjukkan bahwa Wordwall  mampu meningkatkan keterlibatan, motivasi, dan inisiatif belajar siswa, serta berdampak positif pada hasil belajar, termasuk nilai, ketuntasan, dan kemampuan berpikir kritis. Wordwall  sejalan dengan prinsip pembelajaran yang berpusat pada siswa dan mendukung Kurikulum Merdeka, sehingga relevan digunakan dalam menghadapi tantangan pendidikan era digitalta. Kesimpulan dari temuan ini menunjukkan bahwa Wordwall memberikan pengalaman belajar yang menyenangkan, mendorong partisipasi aktif, dan meningkatkan perhatian siswa dalam proses pembelajaran.